The Legal Review of Minister of Religious Affairs Regulation Number 11 of 2019 on the Provision of Performance Allowances in the Ministry of Religious Affairs According to the Principle of Tabadul Manafi - Safpuriyadi, Safpuriyadi; Nurasiah, Nurasiah; Tanjung, Dhiauddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study analyzes the juridical aspects of Minister of Religious Affairs Regulation (PMA) Number 11 of 2019, which addresses the provision of performance allowances in the Ministry of Religious Affairs (Kemenag) from the perspective of the principle of tabadul manafi. Using a normative approach with qualitative descriptive analysis, the research examines how the regulation impacts employee motivation and performance. While the PMA has clearly outlined the mechanisms for performance allowances, including assessment criteria and procedures, it has not significantly improved work ethic and performance, particularly due to the standardized performance achievement requirement. Challenges such as uneven appraisals and insufficient socialization of the regulation have led to administrative inefficiencies. The study recommends periodic evaluations and increased transparency to ensure fair and effective implementation of performance allowances.